LEADERSHIP EXCELLENCE IN HIGHER EDUCATION: PRESENT AND FUTURE - Delener, Nejdet (The journal of contemporary issues in business and government, 2013)
Universities and colleges are expected not only to create knowledge, improve equity, and respond to student needs, but to do so more efficiently and effectively. Hence, to capture the advantage of this more central focus and role, institutions of higher education need to transform their structures, missions, leadership, and processes and programs in order to be more flexible and more responsive to changing social needs. Pivotal to institutional success in achieving this transformation is effective leadership, a critical factor in sustaining and improving universities’ quality and performance. This paper, therefore, examines whether the leaders of higher education are indeed taking the path to success and whether, in doing so, they are implementing a transformational or transactional leadership style. Specifically, this paper aims to systematically review the key findings in the existing literature investigating the styles of and approaches to leadership behaviors that are associated with effectiveness in higher education. The discussion includes a synthesis of the theoretical literature on leadership in higher education and concludes with an overview of potential strategies for educational leaders.